Development of a Real-Time Digital System for Extracting and Monitoring Production Output Data from Machining Processes Using Patlite in the Automotive Manufacturing Industry - Nashiruddin, Muhammad; Sundari, Susanti (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
The advancement of Industry 4.0 has increased the demand for real-time, accurate, and efficient production monitoring systems. This study aims to develop a real-time digital system for extracting production output data from machining processes through the integration of a Patlite signal system within an automotive manufacturing environment. The proposed system utilizes three-color signal indicators (red, yellow, green) as machine status inputs, which are processed through a microcontroller and transmitted via an IoT gateway to a centralized database. A simulation-based experimental approach was employed to evaluate system performance. The results indicate that the system achieved an accuracy level of 96.8% in detecting machine status and reduced manual recording time by approximately 80%. Furthermore, the system enabled real-time monitoring through a web-based dashboard, improving production transparency and decision-making efficiency.This study demonstrates that Patlite signals can be effectively transformed into a reliable digital data source, supporting smart manufacturing implementation. Keywords: IoT, Machining, Patlite System, Production Monitoring, Smart Manufacturing